The Dynamic of Muslim Identity In Multicultural Politic of Australia - M. Mukhsin Jamil; Solihan Solihan; Ahwan Fanani (Jurnal Theologia, 2020)
This research aims to explore the dynamic of Muslim Identities in a multicultural context. Taking Brisbane as a research locus, the research investigates modes of conflict resolution that are enacted in a Muslim minority area by considering the operation of Islam and Islamic modes negotiating identity within the wider society. The prime concern of the research based on the questions of how does the Muslim in Australia expresses their identity by developing the adaptation strategy as social action in a multicultural context?. Based on the questions, this article focused on the issues of the strategy of Muslim that used in responding to view and practices of multiculturalism. This research shows that Muslims in Australia have a wide variety of historical and social backgrounds. Amid Australia's multicultural politics, Australian Muslims have different responses to negotiate Islamic identity on the one hand and as Australian citizens on the other. The adaptation of Muslim in Australia then ranges from a moderate pattern, accepting a secular culture, to being reactionary as the impact of the feeling of being marginalized people as a “stepchild” in Australian citizenship.